2017
DOI: 10.11648/j.ajap.20170602.11
|View full text |Cite
|
Sign up to set email alerts
|

Subliminal Evaluative Conditioning Changed Implicit and Explicit Depressive Cognition

Abstract: Abstract:The purpose of our study was to investigate whether subliminal evaluative conditioning could change implicit and explicit depression-related cognition. Subliminal evaluative conditioning was conducted as a form of Primed Lexical Decision Task, in which subliminally presented self-related word was followed supraminally presented positive words. For measuring implicit depression-related cognition, we used Depression Implicit Association Task (Depression IAT), and for explicit depression-related cognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 30 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Other studies observed similar effect modulations, although less extreme in magnitude [57,58]. These effects suggest that future studies on the clinical potential of pairing procedures, especially when intending to use categorization tasks [65,69,72,85], could benefit from closely examining how an induced processing goal might affect source valence encoding.…”
Section: Processing Goalsmentioning
confidence: 58%
See 4 more Smart Citations
“…Other studies observed similar effect modulations, although less extreme in magnitude [57,58]. These effects suggest that future studies on the clinical potential of pairing procedures, especially when intending to use categorization tasks [65,69,72,85], could benefit from closely examining how an induced processing goal might affect source valence encoding.…”
Section: Processing Goalsmentioning
confidence: 58%
“…Arguably, the appeal of using pairing procedures in clinically relevant domains originates from their initial conception as "implicit" modes of intervention that do not require any conscious processing of target and source stimuli [49,50]. Consistent with this idea, we identified several examples of pairing procedures, particularly among studies on raising self-esteem, that actively attempted to preclude conscious processing by presenting stimuli briefly [65,67,69] or otherwise subliminally [66].…”
Section: Subliminal Stimulus Presentationmentioning
confidence: 64%
See 3 more Smart Citations